Integration of Chatbots for Sales purposes in Kazakhstan: Benefits and Risks - Akhmet, A.T.; Kairat, Y.K. (International School of Economics Maqsut Narikbayev University, Astana, 2024)
This study is aimed at analyzing the use of chatbots based on artificial intelligence (generative AI) in sales in Kazakhstan, their advantages and risks, as well as the potential to improve business processes and customer interaction. The study covers a wide range of types of sales, including retail sales, online commerce, the automotive industry, retail clothing stores, banking, securities and others. The study, conducted on the basis of primary and secondary analysis, examines the introduction of chatbots into various sales sectors in Kazakhstan. The initial study included surveys with representatives of various industries, as well as interview with chatbot developer. The secondary research is based on the analysis of scientific research, books and articles on the topic. It is expected that the results of the study will reveal the effectiveness of chatbots in various industries and provide mitigation plan and recommendations on their integration to increase competitiveness in the market.
Keywords: Chatbots, benefits, risks, artificial intelligence, sales, Kazakhstan, market